Self-perception, learning environment, and learning motivation in physical education outcomes: a literature review - Yopril Daus; Khairudin Khairudin; Sepriadi Sepriadi; Muhammad Arnando (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This literature review examines how self-perception, learning environment, and learning motivation influence Physical Education outcomes in elementary schools. Despite the recognized importance of Physical Education for developing motor skills and promoting lifelong physical activity, variations in student achievement remain poorly understood. Using PRISMA guidelines, fifteen empirical studies published between 2018 and 2025 were selected from international and national databases and analyzed through qualitative thematic synthesis. Findings indicate that positive self-perception enhances students’ engagement and motor performance, supportive learning environments foster autonomy and competence, and intrinsic motivation mediates the translation of psychological and environmental factors into measurable outcomes. However, most studies were cross-sectional, limiting causal inferences, and contextual variations suggest that cultural and pedagogical factors influence these relationships. The review highlights the need for integrated instructional strategies that promote confidence, autonomy, and motivation simultaneously, and recommends longitudinal and experimental studies to clarify causal pathways and optimize evidence-based practices in elementary Physical Education.